2019
DOI: 10.1111/jfpe.13018
|View full text |Cite
|
Sign up to set email alerts
|

Solar drying kinetics and bioactive compounds of blackberry (Rubus fruticosus)

Abstract: In this article, the effect of direct solar drying, indirect solar drying, and freeze drying on the phenolic compound contents and antioxidant capacities of blackberry fruits was investigated. The solar drying kinetics were determined and fitted to six thin layer different mathematical models. The total phenolic, anthocyanin, and flavonoid contents as well as the antioxidant capacity based on ABTS, DPPH, and OH• assays were determined for the dried blackberry samples. The results show that the Midilli–Kuçuk mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…During hybrid solar drying, it is evident that using a high temperature increases moisture reduction(Gupta, Cox, & Abu-Ghannam, 2011). In essence, increasing the temperature enhances moisture evaporation since it increases the heat transfer between the vermicelli and drying air; therefore, moisture removal from the vermicelli increases(Alara, Abdurahman, & Olalere, 2019;López-Vidaña et al, 2019).…”
mentioning
confidence: 99%
“…During hybrid solar drying, it is evident that using a high temperature increases moisture reduction(Gupta, Cox, & Abu-Ghannam, 2011). In essence, increasing the temperature enhances moisture evaporation since it increases the heat transfer between the vermicelli and drying air; therefore, moisture removal from the vermicelli increases(Alara, Abdurahman, & Olalere, 2019;López-Vidaña et al, 2019).…”
mentioning
confidence: 99%
“…Ross et al [ 8 ] reported that the Page model fit the berries’ experimental data drying kinetics. Moreover, López-Vidaña et al [ 12 ] show that the Midilli–Kuçuk model provides the best fit to the experimental data of the solar drying of blackberry because it presented the highest values of R 2 (0.993 and 0.997). Based on our results, we can affirm that the logarithmic model can be used to predict the drying process of blackberry bagasse, and the drying process could be better described when working with temperatures above 70 °C.…”
Section: Discussionmentioning
confidence: 99%
“…The Page model was the best one for the drying processes at 50 • C. Ross et al [8] reported that the Page model fit the berries' experimental data drying kinetics. Moreover, López-Vidaña et al [12] show that the Midilli-Kuçuk model provides the best fit to the experimental data of the solar drying of blackberry because it presented the highest values of R 2 (0.993 and 0.997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all experiments, the temperature inside the solar dryer was about 80% higher compared to the ambient temperature, hence constituting an important parameter to characterize the performance of the device, since the high temperature recorded in the solar dryer favors the drying due to the increase in the evaporation capacity of the dehydration air (Hamdi et al, 2019). This behavior is often reported in direct solar dryers (Santos et al, 2014a;Patil & Gawande, 2018;Hempattarasuwan et al, 2020), since in this type of dryer both the drying air and the sample are heated by the greenhouse effect (Vidaña et al, 2019). During the experiments, temperature fluctuations were observed both in the drying by direct exposure to the sun and in the solar dryer, related to the presence of some clouds, which may affect the incidence of solar radiation according to Hamdi et al (2019).…”
Section: Environmental Conditionsmentioning
confidence: 96%